1997
DOI: 10.1046/j.1365-2672.1997.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of D-ribose production with a transketolase-affected Bacillus subtilis mutant strain in glucose and gluconic acid-based media

Abstract: When the transketolase‐deficient and D‐ribose‐producing Bacillussubtilis strain ATCC 21951 was grown in a glucose (200 g l−1)‐based medium (Kintaka et al. 1986), only 11 g l−1D‐ribose was synthesized, in addition to acetic acid (12 g l−1) and acetoin plus 2,3‐butanediol (24 g l−1), within 1 week of fermentation. After optimizing the process conditions at 2 l fermentor scale (simplified medium composition, pH 5·0 or 6·0, highly oxidative (1000 rev min−1, 3 vvm)), 40 g l−1D‐ribose was obtained from 200 g l−1D‐gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Glucose and corn steep liquor are particularly effective for production of D-ribose [9,32]. To increase D-ribose production, some substrates metabolized only via the pentose phosphate pathway, such as D-gluconic acid, D-xylose, D-xylitol, and D-arabinose, were supplied together with glucose [7,10,28,29]. For example, 50 g l -1 of D-gluconic acid were supplied together with 100 g l -1 of D-glucose to obtain 45 g l -1 of D-ribose in 84 h [10], and the yield of D-ribose was increased from 0.24 to 0.37 mol mol -1 based on total carbon sources consumed.…”
mentioning
confidence: 99%
“…Glucose and corn steep liquor are particularly effective for production of D-ribose [9,32]. To increase D-ribose production, some substrates metabolized only via the pentose phosphate pathway, such as D-gluconic acid, D-xylose, D-xylitol, and D-arabinose, were supplied together with glucose [7,10,28,29]. For example, 50 g l -1 of D-gluconic acid were supplied together with 100 g l -1 of D-glucose to obtain 45 g l -1 of D-ribose in 84 h [10], and the yield of D-ribose was increased from 0.24 to 0.37 mol mol -1 based on total carbon sources consumed.…”
mentioning
confidence: 99%
“…D-Ribose also finds applications in treatment of myocardiac ischemia and certain rare genetic disorders (Gross et al, 1991;Zimmer, 1992;Zimmer et al, 1984). Methods based on chemical or chemo-enzymatic synthesis or fermentation process have been reported for D-ribose production (Bredereck and Rothe, 1938;DeWulf et al, 1997a;Gehrke and Aichner, 1927). However, only the fermentation-based methods have been found to be commercially viable.…”
Section: Introductionmentioning
confidence: 98%
“…1 By partial substitution of D-glucose with D-gluconic acid and by optimizing the process conditions, such as maintaining the pH and highly oxidative conditions, D-ribose productivity was shown to increase four-fold while acetoin concentration decreased two-fold. 9 An independent study has shown improvement in D-ribose productivity by twofold in a fed batch process using a mixture of xylose and glucose with a strain of Bacillus subtilis SPK1. 12 However, the effect of nitrogen substrate on D-ribose production has not been reported.…”
Section: Introductionmentioning
confidence: 98%
“…9 Various carbon sources such as D-glucose, D-sorbitol, D-maltose and D-xylose, and nitrogen substrates such as ammonium sulfate, yeast extract, corn steep liquor and soya flour have been shown to be useful for large-scale D-ribose production. 10 Some organic acids such as sorbic acid have also enhanced the D-ribose productivity due to cell metabolism induction.…”
Section: Introductionmentioning
confidence: 99%